Public Schools and Ghetto Formation in Interwar New Orleans - Walter C. STERN (E-REA)
In New Orleans, racially segregated schools played a central role in the creation of racially distinct neighborhoods beginning with the school building boom that followed World War I. Focusing on the Tremé, Central City, and Broadmoor neighborhoods, this article demonstrates that schools figured prominently in debates over the future of racially mixed neighborhoods, in the formation of isolated black ghettoes, and in the development of white enclaves. In doing so, the article addresses a gap in the historiography of American metropolitan change, which generally overlooks the impact of schools and school policies upon urban development and residential settlement patterns.